Different germanium dopant concentration and the thermoluminescence characteristics of flat Ge-doped optical fibres - Ahmad Fadzil, Muhammad Safwan; Ung, Ngie Min; Bradley, David Andrew; Mohd Noor, Noramaliza (Universiti Putra Malaysia Press, 2017)
The influence of elevated germanium concentration on the thermoluminesence characteristics of a novel form of fabricated flat optical fibre was examined. All the samples were irradiated with two nominal photon energies (6 MV and 10 MV) and 1.25 MeV gamma energy. Flat fibres with 10 mol % Ge concentration provided the superior TL yield compared against that of 6 and 8 mol % Ge-doped optical fibres for both 6 MV and 10 MV energy. Interpretation of the results has been aided by study of the glow curves, revealing in particular new generation of defects in the flat fibres due to strain-generation at the collapsed surfaces. The strain represent deep-energy defects.